If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 5x + 11 = 3x + 22 + 9x + 28 Reorder the terms: 11 + 5x = 3x + 22 + 9x + 28 Reorder the terms: 11 + 5x = 22 + 28 + 3x + 9x Combine like terms: 22 + 28 = 50 11 + 5x = 50 + 3x + 9x Combine like terms: 3x + 9x = 12x 11 + 5x = 50 + 12x Solving 11 + 5x = 50 + 12x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-12x' to each side of the equation. 11 + 5x + -12x = 50 + 12x + -12x Combine like terms: 5x + -12x = -7x 11 + -7x = 50 + 12x + -12x Combine like terms: 12x + -12x = 0 11 + -7x = 50 + 0 11 + -7x = 50 Add '-11' to each side of the equation. 11 + -11 + -7x = 50 + -11 Combine like terms: 11 + -11 = 0 0 + -7x = 50 + -11 -7x = 50 + -11 Combine like terms: 50 + -11 = 39 -7x = 39 Divide each side by '-7'. x = -5.571428571 Simplifying x = -5.571428571
| x-55=23-2x | | 2x-31=3x+7 | | 7(x-1)=18 | | 3x^2+81x-480=0 | | -7k^2+36k+36=0 | | 3x(3)=36 | | 5w+3(w-7)=-37 | | 8x+8=180 | | 3r+3=-6r | | X*2=0.16 | | -47+9x=3x+49 | | f(x)=(x+5)2+4x-7 | | 3.4a=27.2 | | -3(-6)-5=-23 | | (-5h+6)+(3h-3)= | | 2X+3=-(3X+5) | | k(-7)=10t-19 | | 4x-3(2x+4)=x | | 4+2x-(5x+7)-(5x+5)= | | 17x+20=4(4x+7) | | 70+25x=10 | | (x-7)(-5)=15 | | 16=6m | | 20=a^2-8a | | 6c+4-4c+4c= | | 4x-3(2x+4)=c | | 5u-8=62 | | 4(x-8)+12= | | 100+22x=10 | | 267=5(8x+4)+7 | | 2x-12=8-2x | | x+(x+1)=306 |